2012
DOI: 10.1021/ef300904a
|View full text |Cite
|
Sign up to set email alerts
|

Possible Role of Asphaltenes in the Stabilization of Water-in-Crude Oil Emulsions

Abstract: Asphaltene hierarchical aggregation contributes to water-in-oil (W/O) emulsion stability by forming a network structure within thin oil film, separating approaching water droplets. This structure changes the rheology of the film-forming oil to non-Newtonian, which prevents the film drainage at thickness less than about 50–100 nm. It also provides a steric stabilization mechanism to the system. Asphaltenes do not have well-defined hydrophilic heads and hydrophobic tails and, thus, do not have amphiphilic charac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
113
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 109 publications
(118 citation statements)
references
References 24 publications
5
113
0
Order By: Relevance
“…It was reported that rather than whole asphaltenes, only a subfraction of asphaltenes is more likely the real contributor to the stabilization of W/O emulsions. 26,[80][81][82][83][84][85][86] The asphaltenes adsorbed onto clays have also been found to be different in composition from whole asphaltenes. 70,[75][76][77] Therefore, it is important to find ways to extract and study these particular species from asphaltenes, which are mainly responsible for the relevant issues of interest.…”
Section: Extended-sara (E-sara)mentioning
confidence: 99%
“…It was reported that rather than whole asphaltenes, only a subfraction of asphaltenes is more likely the real contributor to the stabilization of W/O emulsions. 26,[80][81][82][83][84][85][86] The asphaltenes adsorbed onto clays have also been found to be different in composition from whole asphaltenes. 70,[75][76][77] Therefore, it is important to find ways to extract and study these particular species from asphaltenes, which are mainly responsible for the relevant issues of interest.…”
Section: Extended-sara (E-sara)mentioning
confidence: 99%
“…However, we acknowledge that the adhesion force magnitude for the asphaltene and corresponding bitumen cases is statistically within the experimental error. Although asphaltenes are expected to be the dominant interfacial component, 6,7 the presence of other indigenous species in bitumen may contribute to the overall adhesion between the two interacting interfaces. 50 The "jump-in" adhesion force at the highest asphaltene concentration may be justified by the increased interpenetration of voluminous asphaltene layers.…”
Section: Force Interactions Between Rigid and Deformable Interfacesmentioning
confidence: 99%
“…1 Steric stabilization from the interfacial asphaltene layers and non-uniform drainage of the intervening liquid films, as water droplets are pressed together, lead to enhanced emulsion stability. [5][6][7] The strongly elastic interfacial layers act as a mechanical barrier between water droplets and must be deformed beyond the shear yield strength to initiate droplet coalescence. 4,5,7,8 Although other bitumen components such as resins and naphthenic acids cannot stabilize water-in-oil emulsions alone, they interact with asphaltenes to enhance emulsion stability.…”
Section: Introductionmentioning
confidence: 99%
“…2,3,4 Asphaltenes and fine bi-wettable solid particles (clays) are known to stabilize such emulsions since they readily partition at the liquid-liquid interface to create mechanical barriers that resist droplet coalescence. [5][6][7][8][9][10][11][12] Recent research has shown that the continual accumulation of asphaltenes at the oil-water interface leads to the formation of elastically-dominated interfacial layers that rupture once a critical yield stress is exceeded. 5,[13][14][15] This yield stress is significantly greater than the typical stress applied during droplet-droplet collision; 16,17 as a result, alternative routes have been explored to reduce the rigidity of these interfacial layers.…”
Section: Introductionmentioning
confidence: 99%